THE ANALYSIS ON PASSIVE VOICE ERRORS ON STUDENTS' THESES AGREED FOR FOLLOWING THE FINAL COMPREHENSIVE EXAM - Zulfariati Zulfariati; Amelia Amelia (Universitas Negeri Padang, 2015)
This article is part of the rvriters' research on the grammatical error analysis. It is the research on the students' theses as the final academic projects for getting the strata one degree at English Department of IKIP UMMY Solok. ldeally the students who have been allowed for joining the final comprehensive exam should be able to write their theses by using correct grammar. However, it was found that some of them still made errors in writing their theses. The aim of this research was to identify the types and percentage of grammatical errors in using passive voice that had been made by the students in their writing products in terms of theses agreed by their advisors for joining the final comprehensive exam. This research was carried out by using descriptive research design. The population of this research was the documents in form of the 81 students' theses which have been agreed for following the final comprehensive exam at three periods of final comprehensive exams from 2012/ 2013 until 2013/2013 at the English Department of FKIP UMMY Solok. Random sampling technique was used to collect 10 theses (about 10% of the population) as the sample. In collecting the data. the reseachers read and analvzed all of the 10 students'theses. It was found that the students made errors in using passive voice in each type of surface strategy taxonomy. The highest level of the students' grammatical error on passive voice usage is on